1988
DOI: 10.3171/jns.1988.69.5.0687
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind placebo-controlled trial of perioperative prophylactic antibiotics for elective neurosurgery

Abstract: In this study, 417 patients undergoing "clean" elective neurosurgical operative procedures were randomized to receive a broad-spectrum antibiotic (piperacillin) or placebo given as three perioperative doses, each 6 hours apart. Randomization was carried out by hospital pharmacists, and the investigators remained blinded until the end of the study. Twenty cases were excluded from analysis because either an unforeseen second operation was performed or antibiotic therapy was initiated within 30 days after surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(39 citation statements)
references
References 17 publications
2
35
0
2
Order By: Relevance
“…Twenty-two full-length papers were reviewed, of which 13 were rejected for the following reasons: studies either enrolled only adults or J Neurosurg: Pediatrics / Volume 14 / November 2014 separate results for children were not provided; 8,10,19,31,41 there was no comparison group; 2 prophylactic antibiotic use was part of a shunt surgery protocol, and thus more than one variable was conceivably being altered; 23,38 clinical shunt infection was not used as the outcome; 7 no details regarding the prophylaxis used were provided; 32 a variety of antibiotics was used (that is, there was no standardization of the prophylaxis protocol); 44 or data specific to shunt surgery were not available. 12,43 Therefore, 9 articles satisfied inclusion criteria for this systematic review and meta-analysis (Table 1). 1,11,18,20,26,27,30,39,40 …”
Section: Search Resultsmentioning
confidence: 99%
“…Twenty-two full-length papers were reviewed, of which 13 were rejected for the following reasons: studies either enrolled only adults or J Neurosurg: Pediatrics / Volume 14 / November 2014 separate results for children were not provided; 8,10,19,31,41 there was no comparison group; 2 prophylactic antibiotic use was part of a shunt surgery protocol, and thus more than one variable was conceivably being altered; 23,38 clinical shunt infection was not used as the outcome; 7 no details regarding the prophylaxis used were provided; 32 a variety of antibiotics was used (that is, there was no standardization of the prophylaxis protocol); 44 or data specific to shunt surgery were not available. 12,43 Therefore, 9 articles satisfied inclusion criteria for this systematic review and meta-analysis (Table 1). 1,11,18,20,26,27,30,39,40 …”
Section: Search Resultsmentioning
confidence: 99%
“…We conducted different analyses to reflect the clinical heterogeneity resulting from interventions that are fundamentally different, separating systemic antibiotics from AIS systems and internal shunts from external drains. Overall, 1684 patients were enrolled in the 15 studies that were included in a meta-analysis in which the effectiveness of systemic antibiotic prophylaxis for internal shunts was evaluated [9,11,12,17,31,50,82,99,100,105,120,121,124,126,128]. Two other trials identified evaluated the use of antibiotic-impregnated catheters for the surgical introduction of ventricular drains, one of which studied the benefit of AIS for internal shunts (110 shunts) [47] and the other evaluated its benefit for external drains (288 drains) [127].…”
Section: Resultsmentioning
confidence: 99%
“…For example, none of the trials included used an intention-to-treat analysis, and $50% of the trials either did not describe the randomization method or it was inadequately described. Only 7 of the studies were double-blinded using identical-appearance interventions [11,17,50,82,99,120,121]. The attrition rate was $5%.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of SSI in patients after neurosurgical intervention is between 1.25% and 17% in condition of prophylactic administration of antibiotics, and 0.3% to 3.0% without antibiotic prophylaxis [2, 12,4,13,14,31,32].…”
Section: Discussionmentioning
confidence: 99%